The Prevalence of Depression and its Associated Demographic Factors in the Elderly with Electronic Health Records in Zanjan - Pourrahimi A; Sheikhlar A; Keshavarz Afshar M; Abdi M; Aghajanloo A; Mohammadi S; Bayat F (Zanjan University of Medical Sciences and Health Services, 2018)
Background: The highest prevalence of depression is observed in the elderly, and the cultural difference in each region causes a difference in the incidence of this disorder. Objectives: Therefore, this study aimed to investigate the prevalence of depression and its associated demographic factors in the elderly with electronic health records in Zanjan during 2018. Methods: A total of 400 elderly people with electronic health records participated in this descriptive cross-sectional study, who were selected by the cluster random sampling method from 18 urban community health centers of Zanjan. The data were collected using a demographic questionnaire and the geriatric depression scale(. Finally, data entered the SPSS software and analyzed utilizing descriptive statistics, as well as Chi-square, ANOVA, and logistic regression tests. Results: The mean age of the elderly was 77.7±5.56 and 68.5% of them had some degrees of depression, including mild (40.5%), moderate (19.2%), and severe (8.8%) depression. Mild depression was more prevalent among younger adults while moderate to severe depression was common in older adults over 75. The results revealed that depression had a significant relationship with age and educational level while not having any significant relationship with sex, marital status, and the dwelling place. Conclusion: Considering the high prevalence of depression among the elderly in Zanjan, health managers re suggested to prioritize educational programs and social support for this group of individuals and monitor the performance of supportive institutions such as insurance in this rgard. Eventually, they are recommended to pay attention to the geographical and cultural diversity of different regions of the country to reduce the elderly's depression level